Highly sensitive and selective room-temperature NO2 gas-sensing characteristics of SnOX-based p-type thin-film transistor - Jeong, Hwan-Seok; Park, Min-Jae; Kwon, Soo-Hun; Joo, Hyo-Jun; Kwon, Hyuck-In (Sensors and actuators. B, Chemical, 2019)
•A p-type metal oxide semiconductor-based TFT-type gas sensor was studied for the first time by using SnOX for both the channel and sensing layers.•The fabricated SnOX TFT gas sensor showed a maximum response value of 19.4–10 ppm NO2 at room temperature (RT).•This maximum response value is significantly higher than the maximum response values of previously reported p-type MOS-based NO2 sensors.•The importance of this work is in the successful fabrication of highly selective and sensitive p-type NO2 gas sensor at RT via RF sputtering process. The high-performance p-type metal-oxide-semiconductor (MOS)-based gas sensor is an important subject of research in the field of gas-sensing technology. In this work, we demonstrated a p-type MOS-based thin-film transistor (TFT) nitrogen dioxide (NO2) gas sensor that used tin oxide (SnOX) for both the channel and sensing layers. The crystalline status, surface morphology, and atomic-bonding configuration of the thin-film were examined using X-ray diffraction, field emission-scanning electron microscopy, and X-ray photoelectron spectroscopy. The results indicated that the deposited thin-film was mainly composed of polycrystalline SnO with a tetragonal structure. The fabricated p-type SnOX TFT showed a maximum response value of 19.4-10 ppm NO2 at room temperature (RT, 25 °C) when operated in the subthreshold region, which was significantly higher than that of 2.8–10 ppm NO2 obtained from a p-type SnOX thin-film chemiresistor at RT. In addition, the SnOX TFT gas sensor showed significantly higher sensitivity to NO2 gas than to other target gases such as NH3, H2S, CO2, and CO at RT. To the best of our knowledge, this is the first study to a p-type MOS-based field-effect transistor-type gas sensor. Our experimental results demonstrate that the p-type SnOX TFT is a promising gas sensor that can operate at RT with high sensitivity and selectivity to NO2 gas.